E-Readiness on Application E-Government in Establishing Smart Governance at Bandung City Communication and Information Services Agency - Hidayat, Asep; Sofiani, Anisa (Journal of Governance, 2024)
Implementation of e-government requires readiness in various factors, from finances and employee competency in the ability to use technology to the availability of infrastructure to support the implementation of e-government. This readiness is an essential factor in determining the success of e-government. Implementation readiness is an important factor in e-government, referred to as e-readiness. The purpose of this research is to find out and analyze strategy assessment (strategy), technology (technology), organization (Organization), human resources (people), as well as environmental assessments (environment) carried out by the Bandung City Diskominfo in implementing E-Government to create Smart Governance. The research theory used in this research is the E-Readiness readiness theory using the STOPE framework model (Strategy, Technology, Organization, People, Environment), which includes a technology readiness scale based on a systematic model developed by (Al Osaimi et al., 2006). The method used in this research uses a descriptive method with a qualitative approach. Research data collection is based on observation, interviews, and documentation.  The results of this research show that the Bandung City Diskominfo has an Overall STOPE Grade of 2.33 on a scale of 4, which indicates that the level of readiness of this institution is at level 2 or the "average" category according to the assessment scale developed by Al-osaimi in 2006. It can be concluded that the implementation of e-government in 1) strategy assessment still lacks coordination between employees; 2) assessment of device technology is inadequate; 3) assessment organization still not adapted; 4) assessment people not all human resources understand e-government; 5) assessment environment still not everyone understands the concept e-government.